PENGARUH PENERAPAN TATA KELOLA, RASIO LIKUIDITAS, DAN TINGKAT EFISIENSI TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PERBANKAN DI BEI - Bella Martina Wardani; Sunu Priyawan; Slamet Riyadi (Jurnal Manajerial, 2019)
This study aims to analyze the influence of Corporate Governance, liquidity ratios and efficiency levels on financial performance and company value that can be used as a reference for management in using good and appropriate governance so that it can benefit the company as a whole. The population in this study uses all banking companies listed on the Indonesia Stock Exchange with a sample of 21 companies. The variables used in this study are Corporate Governance that is proxied by the Board of Commissioners, Independent Board of Commissioners, Board of Directors and Audit Committee, Liquidity Ratios that use the proxy Current Ratio, Quick Ratio and Cash Ratio, Efficiency Levels that use Operational Cost-Operational Proxies , Financial Performance that uses the proxy of Return On Assets (ROA), Return On Equity (ROE) and Net Profit Margin (NPM), while the company value uses Price to Book Value (PBV), Price Earning Ratio (PER) and TOBIN'S. using Smart PLS (Partial Least Square) analysis tool to determine the effect of these variables. The results of this study indicate that Corporate Governance has a significant negative effect on Financial Performance and Corporate Values, Liquidity Ratios and Efficiency Levels have a significant positive effect on Financial Performance and Corporate Value While Financial Performance has a significant negative effect on Firm Value